Mixing of non-swirling and swirling inclined dense jets - Jiang, Mingtao (2018)
The high salinity brine discharge from large scale SWRO desalination plants is potentially harmful to the local marine ecosystem and therefore needs to be mixed well with the ambient water to meet the environmental requirements. At present, full submergence of the dense jet is generally targeted as the typical design scenario for brine disposal. Due to its engineering importance, the configuration had also been extensively studied in the past two decades.